Tribological and milling performance of NbC–Ni films deposited by sputtering with different Ni contents. (July 2020) - Varela, L.B.; Cavaleiro, A.; Tschiptschin, A.P.; Gangopadhyay, S.; Fernandes, F.
Abstract: This work focuses on the effect of Ni on the tribological and milling performance of NbC–Ni films deposited by reactive magnetron sputtering. High temperature tribological performance of films was studied through reciprocating dry sliding experiments. The milling performance of the coatings was evaluated in a CNC machining center. Results showed that the coefficient of friction of the Nb0.43 Ni0.13 C0.44 film was the lowest at room temperature, whereas, at high temperature, it was not significantly changed for the films with lower Ni content. It decreased for the Nb0.36 Ni0.24 C0.40 film. The flank wear resistance was enhanced when compared to the uncoated tool. Crater wear and severe chipping were the main wear mechanisms observed for the uncoated tool, while the coated tools evidenced mainly adhesive and abrasive wear and nose chipping. Highlights: Nb0.43 Ni0.13 C0.44 coatings shows the lowest wear rates during reciprocating tests. NbC + Ni coated inserts mitigated the tool wear observed on uncoated samples. Flank wear of Nb0.43 Ni0.13 C0.44 coated inserts was 70% lower than uncoated inserts. Flank wear of Nb0.43 Ni0.13 C0.44 coated inserts was 60% lower than those NbC coated. NbC/NbNiC coated inserts performance correlated with their tribological properties.